Knowledge and Practices of Infant and Toddler Weaning among Mothers Attending Pediatrics Department of A Tertiary Care Hospital In Lahore - Wizra Faiz, Zahra Fayyaz, Noah Mutai, Sikandar Javed Bajwa, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the weaning knowledge, practices and the influencing factors. Methods: Questionnaires were filled from 315 mothers with children aged 06-24 months, who visited Pediatrics OPD Services Hospital, Lahore, Pakistan in 4 months. Weaning knowledge and practices of the respondents were evaluated by using a pre-tested questionnaire. Chi-square test was used to assess the associations between the variables. It was ranked as good, satisfactory and poor based on the gross sum total. Results: The overall knowledge of weaning was good in 159(50.5%) mothers and 133(42.2%) had satisfactory knowledge. Whereas the practices of 152(48.3%) mothers out of 315 were good but poor in 46(14.6%) of the mothers. There is a statistically significant association between the knowledge and practices of weaning with age of children (p values= 0.000 and 0.000, respectively) and total number of children of the respondents (p-values= 0.000 and 0.000, respectively). Residential status of respondent (p-value=0.028) and educational status of mothers (p-values= 0.01) also showed significant association with mothers knowledge. Outcome variables (p-values=0.02 and p-value= 0.026 respectively) are also statistically significant with the source of information and weaning practices. We also found an association with the type of family of the respondent (p-value=0.034). Conclusion: These findings will be helpful in making strategies of awareness program so that the effects of pre- or post-weaning can be minimized.